Synthesis of Alkyd Resin Through Alcoholysis – Polyesterification Process from Used Cooking Oil Pretreatment Using Alkaline Activated Natural Bayah Zeolite - Suhendi, Endang; Heriyanto, Heri; Fitri Asyuni, Nadya; Kiki Shahila, Ilham (World Chemical Engineering Journal, 2022)
Waste cooking oil can be treated by an adsorption process using Bayah natural zeolite as raw material for alkyd resin synthesis. This study aimed to determine the optimum conditions for the equivalent ratio of OH:COOH and the temperature of the alkyd resin synthesis. The research was carried out by preparing used cooking oil and Bayah natural zeolite (BNZ), adsorption process, and alkyd resin synthesis through the alcoholysis-polyesterification process. The optimum addition of Bayah natural zeolite-activated NaOH 0.75 N in pretreatment waste cooking oil is 30% weight in terms of color, density, viscosity, and functional group characteristics of the resulting alkyd resin. The characteristics of the alkyd resin product at optimum conditions obtained light brown color with an OH: COOH equivalent ratio of 1.4, and the alcoholysis and esterification temperature at 190 oC with a density value is 1.112 g/cm3, FFA value is 0.1528%, viscosity value is 4808 cP. The ester functional group at wavelengths 1267 cm-1 and 1722 cm-1, the 1H NMR spectrum of the ester group at the peak of 3.5 ppm, and a functional group of 7.6 ppm.